2007
DOI: 10.1161/01.str.0000259661.05525.9a
|View full text |Cite
|
Sign up to set email alerts
|

Missed Diagnosis of Subarachnoid Hemorrhage in the Emergency Department

Abstract: Background and Purpose-Subarachnoid hemorrhage (SAH) can be devastating, yet its initial presentation may be limited to common symptoms and subtle signs, potentially leading to misdiagnosis. Little is known about population rates of misdiagnosis of SAH, or hospital factors that may contribute to it. We estimated the population-based rate of missed SAH among emergency department (ED) patients and examined its relationship with hospital characteristics. Methods-We studied persons admitted with a nontraumatic SAH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
108
0
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(120 citation statements)
references
References 43 publications
5
108
0
7
Order By: Relevance
“…8 Physicians in the emergency department, when surveyed, have stated that 99% sensitivity is acceptable for a subarachnoid hemorrhage rule, a threshold that acknowledges the pitfall of pursuing diagnostic perfection at all cost. The narrow confidence bands of sensitivity for the Ottawa SAH Rule bracket this extremely high threshold, and the point estimate exceeds it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Physicians in the emergency department, when surveyed, have stated that 99% sensitivity is acceptable for a subarachnoid hemorrhage rule, a threshold that acknowledges the pitfall of pursuing diagnostic perfection at all cost. The narrow confidence bands of sensitivity for the Ottawa SAH Rule bracket this extremely high threshold, and the point estimate exceeds it.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 However, a population-based study involving patients admitted to hospital through emergency departments in Ontario with a most responsible diagnosis of nontraumatic subarachnoid hemorrhage found that over 5% of confirmed subarachnoid hemorrhages were missed at initial presentation, especially in smaller hospitals. 8 Therefore, identifying which patients with headache require investigations to rule out this catastrophic diagnosis, and which do not, is a critical decision in emergency medicine.…”
mentioning
confidence: 99%
“…These issues may contribute to suboptimal work-ups and may account for the persistence of an basal rate of ''missed bleeds'' that was recently demonstrated to be 5% of acute headache patients in Canadian EDs. 39 …”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Misdiagnosis can result in both poor patient outcomes and litigation. 3,5 The diagnostic algorithm for SAH is noncontrast brain computed tomographic study (CT), followed by lumbar puncture (LP) if the CT is normal or nondiagnostic.…”
mentioning
confidence: 99%